Non-Mydriatic Fundus Retinography in Screening for Diabetic Retinopathy: Agreement Between Family Physicians, General Ophthalmologists, and a Retinal Specialist - Cunha, Leonardo Provetti; Figueiredo, Evelyn Alvernaz; Araújo, Henrique Pereira; Costa-Cunha, Luciana Virgínia Ferreira; Costa, Carolina Ferreira; Neto, José de Melo Costa; Matos, Aline Mota Freitas; Oliveira, Marise Machado de; Bastos, Marcus Gomes; Monteiro, Mário Luiz Ribeiro (Frontiers in Endocrinology, 2018)
Purpose: to determine the level of agreement between trained family physicians (FPs), general ophthalmologists (GOs) and a retinal specialist (RS) in the assessment of non-mydriatic fundus retinography in screening for diabetic retinopathy (DR) in the primary health care setting. Methods: 200 diabetic patients were submitted to two-field non-mydriatic digital fundus camera. The images were examined by 4 trained FPs, 2 GOs and 1 RS with regard to the diagnosis and severity of DR and the diagnosis of macular edema. The RS served as gold standard. Reliability and accuracy was determined with the Kappa test and diagnostic measures. Results: A total of 397 eyes of 200 patients were included. The mean age was 55.1 (± 11.7) years and 182 (91%) had type-2 diabetes. The mean levels of serum glucose and glycosylated hemoglobin A1c were 195.6 (±87.3) mg/dL and 8.9% (±2.1), respectively. DR was diagnosed in 166 eyes by the RS and in 114 and 182 eyes by GO1 and GO2, respectively. For severity, DR was graded as proliferative in 8 eyes by the RS vs. 15 and 9 eyes by GO1 and GO2, respectively. The agreement between the RS and the GOs was substantial for both DR diagnosis (GO1 k=0.65; GO2 k=0.74) and severity (GO1 k=0.60; GO2 k=0.71), and fair or moderate for macular edema (GO1 k=0.27; GO2 k=0.43). FP1, FP2, FP3 and FP4 diagnosed DR in 108, 119, 163 and 117 eyes, respectively. The agreement between the RS and the FPs with regard to DR diagnosis was substantial (FP2 k=0.69; FP3 k=0.73; FP4 k=0.71) or moderate (FP1 k=0.56). As for DR severity, the agreement between the FPs and the RS was substantial (FP2 k=0.66; FP3 k=069; FP4 k=0.64) or moderate (FP1 k=0.51). Agreement between the FPs and the RS with regard to macular edema was fair (FP1 k=0.33; FP2 k=0.39; FP3 k=0.37) or moderate (FP4 k=0.51). Conclusions: Non-mydriatic fundus retinography was shown to be useful in DR screening in the primary health care setting. FPs made assessments with good levels of agreement with a RS. Non-mydriatic fundus retinography associated with appropriate general physicians training is essential for the DR screening.